Analisis Resiko dan Program Keselamatan dan Kesehatan Kerja (K3) Pada Pabrik Sagu CV Makmur Timika - Akely, Nelci Esterlina; Taime, Habel (STIE Jambatan Bulan, 2022)
This study aims to determine the application of work safety (K3) at CV Makmur Timika. The data collection methods are interviews and observations while the analytical tools use the Job Safety Analysis (JSA) method. Based on the results of research on the application of K3 at CV Makmur Timika, it shows that the production process from the forest to the sago factory has potential hazards such as mechanical hazards, ergonomic hazards, chemical and microbiological hazards, and other occupational diseases that can be harmful to workers. Researchers suggest to the management of CV Makmur Timika to continue to improve work safety and health by making efforts to control various potential hazards in every job, especially in the forest and factory work processes such as using Personal Protective Equipment (PPE) while working, obeying work procedures and being careful be careful when working